The Association of Maternal Accompaniment at Family Dinners and Depressive Symptoms of Korean Adolescents - Lee, Jae-Young (Int J Environ Res Public Health, 2020)
This study aims to investigate the association between family dinners involving the participation of both mother and her adolescent child and depressive symptoms within the adolescents. Data from 2183 mother–child pairs obtained from the Korea National Health and Nutrition Examination Survey IV–VI (2010–2013, and 2015) were employed in the analysis. The dependent variable of this study was depressive symptom of adolescents. Maternal accompaniment at family dinners was the variable of interest. Logistic regression analysis was performed to calculate odds ratios (ORs) and 95% confidence intervals (CI) to analyze the association between family dinners including both mother and adolescent and depressive symptoms within the adolescent. According to the results, maternal absence in family dinners was significantly associated with higher odds of depressive symptoms in adolescents (OR = 1.42, 95%CI: 1.01–1.99). In particular, the association was strong among adolescents aged 12–15, female adolescents, those with mothers without depressive symptoms, and city dwellers. This study showed that maternal absence at family dinners was strongly associated with depressive symptoms of adolescents. For the sake of adolescent mental health, it may be necessary to consider the implementation of policies that emphasize the importance of maternal accompaniment at family dinners and encourage the presence of mothers at the dinner table.